The impact of pricing and patent expiration on the demand for pharmaceuticals: An examination of the use of broad-spectrum antimicrobials - Klaus Kaier (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2010)
The aim of the analysis was to determine whether demand in Germany for antibiotics is driven by prices that drop considerably when generic substitutes become available. A time-series approach was therefore carried out to explore price elasticities of demand for two different classes of broad-spectrum antimicrobials (fluoroquinolones and cephalosporins) using data on ambulatory antibiotics prescribed on the German statutory health insurance scheme and data on in-hospital antibiotic use in a German teaching hospital. In short, we attempted to explain demand for different antibiotics based on changes in price, patent expiration and hospital-wide morbidity. The analyses demonstrates that patent expiration is followed by substantial decreases in the price of antibiotics. In the outpatient sector, all antibiotics included in the analysis showed significant negative own-price elasticities of demand. However, in the hospital settings, significant own-price elasticities were only determined for some antibiotics although price decreases were stronger than in the outpatient sector. We conclude that price dependence of demand for antimicrobials is present both in the ambulatory and the hospital setting. However, it is especially problematic in the hospital setting because price differences among the antibiotics observed are particularly small compared to the overall cost of hospitalisation.
Keywords: I11; L65; 330